Recent Advances in the Synthetic Utility of ortho-Quinone Methides for Cyclization Reactions: A Versatile Skeleton - Hou, Qinggao; Liu, Xianping; Chen, Liyong; Cao, Renfeng; Yue, Sitong; Zhu, Longzhi; Xiong, Biquan (Current Organic Chemistry, 2025)
In the past decade, the field of ortho-quinone methides (o-QMs) has witnessed remarkable advancements, underscoring their pivotal role as synthetic intermediates in organic chemistry. These electrically neutral species, distinguished by a cyclohexadiene moiety conjugated with a carbonyl and an exo-methylene group, possess an aromatic zwitterionic resonance structure. This unique framework endows them with a pronounced electrophilicity, particularly at the 1,4-positions. The rich chemistry of o-QMs encompasses three principal reaction modalities: 1,4-conjugated addition, [4 + X] cycloaddition (X = 1, 2, 3, etc.), and oxa-6π-electrocyclization pathways. Specifically, the synthesis of chromane derivatives is achieved through [4 + 2] cycloaddition and subsequent oxa-6π-electrocyclization, whereas benzofuran derivatives are accessed via the [4 + 1] cycloaddition route. This review provides a systematic summary of the latest advancements in cycloaddition reactions involving ortho-quinone methides and their derivatives. It offers an in-depth analysis of the substrate diversity and potential reaction mechanisms underlying these transformations. The cycloaddition reactions presented herein are uniformly characterized as ionic systems, with the tautomerization between the oxygen anion generated subsequent to the deprotonation of o-QMs and the resulting carbonyl group identified as a pivotal step for reaction activation. Moreover, we have expanded on the discussion to include a detailed examination of drug intermediate compounds derived from o-QMs. These skeletal derivatives are highlighted for their growing utility in the realm of drug design and synthesis, effectively bridging the divide between foundational research and pharmaceutical applications. We aspire to stimulate the evolution and innovation of synthetic methodologies that leverage o-QMs as scaffolds. By in-depth investigation of the o-QMs-mediated cyclization reactions, we aim to offer theoretical insights that will guide the synthesis of intricate (chiral) cyclic compounds, thereby, enhancing the practical application of o-QMs in both chemical research and medical development.
Keywords: tautomerization